MODEL V UNTUK PERANGKAT LUNAK MANAGEMENT PENDAFTARAN ANGGOTA DI PERPUSTAKAAN DAERAH KABUPATEN KUDUS - Esti Wijayanti; Dhevie Novita Sari (Jurnal DISPROTEK, 2018)
The information technology development is growing fast. The books are the main learning for people who extremely need information. The library in Kudus is meant as an infrastructure . Registration flow that has been happening is manual registration and directly submit the terms and fill out the registration form. Given the rapid development of information the researcher will analyze the conceptual registration process into the account management system of the book keeping and will produce a member registration processing system and borrowing as well as the return of books in the library and archives of the regency of Kudus city. The software will be developed with the Microsoft Visual Studio tools (VB.Net). For the design of this system management application using the V model so easy to design this software. With the application of this software is expected to improve the quality of service, improve efficiency and effectiveness of data source management and improve services